2010
DOI: 10.1007/s00125-010-1708-x
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocellular lipid accumulation is associated with permanent relocation ex vivo and in vitro of fatty acid translocase (FAT)/CD36 in obese patients

Abstract: Aims/hypothesis Intramyocellular lipids (IMCL) accumulation is a classical feature of metabolic diseases. We hypothesised that IMCL accumulate mainly as a consequence of increased adiposity and independently of type 2 diabetes. To test this, we examined IMCL accumulation in two different models and four different populations of participants: muscle biopsies and primary human muscle cells derived from non-obese and obese participants with or without type 2 diabetes. The mechanism regulating IMCL accumulation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
101
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 50 publications
10
101
1
1
Order By: Relevance
“…Palmitate oxidation was measured as production of 14 CO 2 and 14 C-ASMs from [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]-palmitate (1 mCi/mL), nonlabeled palmitate (100 mmol/L), and 1 mmol/L carnitine after 3 h. Lipids were extracted from the myotubes, and lipid incorporation was measured by thin-layer chromatography. Bands corresponding to TAG and diacylglycerol (DAG) were quantified by liquid scintillation as previously described (16).…”
Section: In Vitro 14 C-palmitate Oxidation and Lipid Incorporationmentioning
confidence: 99%
See 2 more Smart Citations
“…Palmitate oxidation was measured as production of 14 CO 2 and 14 C-ASMs from [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]-palmitate (1 mCi/mL), nonlabeled palmitate (100 mmol/L), and 1 mmol/L carnitine after 3 h. Lipids were extracted from the myotubes, and lipid incorporation was measured by thin-layer chromatography. Bands corresponding to TAG and diacylglycerol (DAG) were quantified by liquid scintillation as previously described (16).…”
Section: In Vitro 14 C-palmitate Oxidation and Lipid Incorporationmentioning
confidence: 99%
“…Hulver et al (5) used such a model to demonstrate that myotubes of nondiabetic, severely obese individuals retain abnormal lipid partitioning (i.e., elevated triacylglycerol [TAG]-to-blunted fatty acid [FA] oxidation ratio) (5). Of note, Aguer et al (6) showed that T2D subjects had increased IMCL content in muscle tissue and that this elevation was maintained in primary myotubes from these subjects compared with obese nondiabetic control subjects, indicating that increased IMCL content is preserved in vitro. However, the underlying reason for this finding was not examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suggestions [2,3] that mitochondrial dysfunction is a determinant of intramuscular lipid accumulation and insulin resistance have been questioned [4][5][6][7][8]. In contrast, evidence for the excess influx of fatty acids [6,[9][10][11] and for an inability to completely oxidise them [12,13] provides an alternative explanation for intramuscular lipid accumulation in insulin-resistant muscle.…”
Section: Introductionmentioning
confidence: 99%
“…oxidation or esterification). Several studies have associated skeletal muscle sarcolemmal FAT/CD36 with insulin resistance in animals and in humans [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%